Aplicação do modelo WEAP na avaliação de alocação de água do reservatório dos Pequenos Libombos, Moçambique - Notisso, Pedro Francisco (2020)
The issue of satisfying human and environmental water needs has been tackled in the water resources management and planning framework in the Africa Austral. Currently, the Umbeluzi river basin is Greater Maputo main source of water supply. This study was driven by uncertainties generated by difficulties in meeting future water needs. What can happen to water supply if the patterns of population growth, industrial growth and increase in irrigation areas change? This article aims at assessing the capacity of meeting water needs in the Greater Maputo area in Mozambique through application of WEAP (Water Evaluation and Planning System). WEAP is a model that allows simulation of water resource systems with multiple uses in an integrated manner. The case study is the Mozambican part of the Umbeluzi River basin. Four scenarios were simulated: the reference scenario which corresponds to the on-going exploitation; three impact scenarios: Lower Growth that represents lower values of growth of consumption sites, Trend that reflects average growth values of consumption sites and Greater Growth which corresponds to higher values of population growth, expansion of the agricultural and industrial area, between 2018 and 2040 and adaptation measure. The methodology included the estimation of affluences to the system obtained from the results of the Water Year Method. An assessment of the capacity to meet water needs was made using indicators such as coverage and supply guarantee. The results obtained show the system's inability to meet current and future needs. The system has an annual water supply guarantee of 70.9% and 63.5% in the Reference and Lower Growth scenarios, with more critical values of 42.1% and 31.7% in the Trend and Higher Growth scenarios. All scenarios have an average duration of each failure exceeding three months.